Identification Escherichia coli on some fisheries commodities in the traditional market of Mamuju, West Sulawesi - Ruqayyah Jamaluddin; Nurfadilah Nurfadilah; Sunarti Sunarti (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
Fish is a source of high-quality protein. Protein in fish has a complete composition and amount of essential amino acids. However, fish is a type of food that is susceptible to biological damage and is susceptible to microbial contamination so that it quickly decays. One of the most important microorganisms in spoilage of fish meat is Escherichia coli bacteria. This study aims to determine the presence of Escherichia coli bacteria in scad, tuna and skipjack tuna. The research was carried out from July to September 2021. The research method used was a sample survey method, sampling was carried out at 3 market locations, namely the TPI market and the tasiu market. Furthermore, the samples were analyzed at the Laboratory of Fish Quarantine and Quality Control Center (BKIPM) Mamuju, West Sulawesi. The results showed that the largest E.coli content was found in tuna 1 in the TPI market, which was 20 MPN/g, and the smallest E.coli content was < 3 MPN/g, namely scad fish 1 in the tasiu and TPI markets, tuna 1 and 2 in the TPI market, tuna 2 in TPI market.